Photocatalytic of N-doped TiO2 Nanofibers Prepared by Electrospinning - Sineenart Suphankij; Wanichaya Mekprasart; Wisanu Pecharapa (My University, 2013)
Nitrogen-doped TiO2 nanofibers were prepared by electrospinning process using ammonium acetate (CH3COONH4) as nitrogen sources and titanium (IV) isopropoxide (TiP) in 2-methoxyethanol as starting precursor. The different amount of nitrogen in TiO2 was introduced into the fibers. The structural properties of nitrogen-doped TiO2 nanofibers were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), and X-ray photoelectron spectroscopy (XPS). XRD results indicated that the crystallinity of as-prepared fibers and after calcined corresponds to phase of TiO2 independent on nitrogen content. XPS indicates that nitrogen was doped effectively into the fibers. Nitrogen-doped TiO2 nanofiber materials were utilized as the photocatalyst in dye photodegradation under visible light. The significant absorption enhancement in visible region was obtained by nitrogen-doped TiO2 nanofibers relating to the improvement of photocatalytic efficiency comparing to undoped-TiO2.
Keywords: Electrospinning; Photodegradation; Titanium Dioxide; TiO2 Photocatalysis and Solar Cells